The Raman optical activity of β-d-xylose: where experiment and computation meet1. Issue 34 (14th September 2015) - Zielinski, François; Mutter, Shaun T.; Johannessen, Christian; Blanch, Ewan W.; Popelier, Paul L. A.
<x xml:space="preserve">Abstract</x> By further refining our DFT/MM protocol that allows for the crucial influence of hydration, we show that it is possible to achieve near-perfect agreement between observed and calculated ROA spectra.